1983
DOI: 10.1128/jvi.45.1.10-17.1983
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of herpes simplex virus genes in vivo: overlap of a late promoter with the 3' end of the early thymidine kinase gene

Abstract: We identified in herpes simplex virus type 1-infected cells six cytoplasmic transcripts which were complementary to BamHI restriction endonuclease fragment Q. Two transcripts appeared in major amounts compared with the other four. One major transcript of about 1.4 kilobases was the mRNA for the viral thymidine kinase, was synthesized at intermediate times, and was classified as a beta transcript. The other major transcript was synthesized at late times and was classified as a gamma transcript. This late transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
14
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 26 publications
4
14
0
Order By: Relevance
“…Sharp et al (31) recently reported that the levels of HSV thymidine kinase mRNA decrease late in infection, a fact consistent with the reduced rates of thymidine kinase activity observed by others (12). The HSV glycoproteins are structural proteins, and some clearly belong to the y class.…”
supporting
confidence: 58%
“…Sharp et al (31) recently reported that the levels of HSV thymidine kinase mRNA decrease late in infection, a fact consistent with the reduced rates of thymidine kinase activity observed by others (12). The HSV glycoproteins are structural proteins, and some clearly belong to the y class.…”
supporting
confidence: 58%
“…1C, right). Another L transcript, that of gH, is known to be colinear with a transcript arising from the E gene tk, located upstream of gH (17,19,46). To determine the level of promoter-specific RNA from gH, we asked if potential contributions to the QRPCR measurement from upstream run-on transcripts could be subtracted.…”
Section: Resultsmentioning
confidence: 99%
“…With lacZ upstream of the albumin enhancer/promoter, it is very unlikely that read-through transcription from the TK promoter could occur. The 3Ј untranslated region of TK, downstream of the ICP4 transgene, overlaps the 5Ј promoter region of gH (65), which should have no impact on the regulation of ICP4 expression. pTK⌬L-ALI4 was cotransfected with d120 DNA into E5 (ICP4 ϩ ) cells, and the resulting recombinant viruses were thrice plaque purified on E5 cells.…”
Section: Resultsmentioning
confidence: 99%
“…The second chimeric transgene, with the Escherichia coli lacZ gene under control of the HSV-1 TK promoter, was used to easily screen for recombinant viruses and identify cells containing replicating virus. TK is an E gene, and therefore lacZ expression should be dependent on synthesis of ICP4 protein (11,16,57,65,78). The chimeric transgenes (albumin enhancer/promoter-ICP4, TK promoter-lacZ) were inserted into the HSV-1 TK gene (UL23), resulting in a 0.5-kb deletion of the TK gene and inactivation of the UL24 gene (31).…”
mentioning
confidence: 99%